Positive electrode material precursor and preparation method thereof, lithium ion battery positive electrode material and lithium ion battery
By designing a positive electrode material precursor with a specific internal structure, the problems of unstable structure of high nickel positive electrode material and insufficient lithium ion transmission channels are solved, and lower battery internal resistance, higher magnification and cycling performance and better Safety performance.
Patent Information
- Application Number
- CN202211584731.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-09
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-12-09
AI Technical Summary
The existing high-nickel positive electrode material has unstable structure, resulting in poor safety performance and insufficient lithium ion transmission channels, resulting in high internal resistance of the battery and poor rate performance and cycle performance.
Design a positive electrode material precursor, which is arranged in sequence from the inside to the outside, the inner core includes a loose first inner layer and a dense second inner layer, the coupling layer is loose and the outer shell is dense, through this structure Adjust the contact area between the lithium ion transport channel and the electrolyte.
By adjusting the internal structure of the precursor, the internal resistance of the battery is reduced, the rate performance and cycle performance are improved, and the safety performance is improved, and the capacity retention rate and lower initial internal resistance are achieved.
Smart Images

Figure CN115771916B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium-ion batteries, and in particular to a positive electrode material precursor and a preparation method thereof, a lithium-ion battery positive electrode material and a lithium-ion battery. Background Art
[0002] With the continuous development of the new energy industry, lithium-ion batteries have received extensive attention and research as a new type of green battery. The performance of positive electrode materials directly affects the capacity, cycle and safety performance of lithium-ion batteries.
[0003] High nickel cathode materials have a high energy density. Generally, the higher the nickel content, the more unstable the material structure and the worse the safety performance. In view of this, by designing the internal structure of the precursor, the contact area between the cathode material and the electrolyte is adjusted, the lithium ion transmission channel is increased, and the diffusion path of lithium ions is shortened, so as to reduce the internal resistance of the battery and improve the rate performance and safety performance. Summary of the invention
[0004] The purpose of the present application is to provide a positive electrode material precursor and a preparation method thereof, a lithium ion battery positive electrode material and a lithium ion battery to solve the above problems.
[0005] To achieve the above objectives, this application adopts the following technical solutions:
[0006] A positive electrode material precursor comprises a core, a connecting layer and a shell arranged in sequence from the inside to the outside;
[0007] The inner core includes a first inner layer and a second inner layer, the first inner layer is loose, and the primary particles are needle-shaped; the second inner layer is dense, and the primary particles are needle-shaped; the connecting layer is loose, and the primary particles are spindle-shaped or thin strips; the outer shell is dense, and the primary particles are spindle-shaped.
[0008] Preferably, the primary particles of the inner core and the connecting layer are arranged in a disordered manner, and the primary particles of the outer shell are arranged in a radially divergent manner.
[0009] Preferably, the average pore size of the first inner layer is 20nm-200nm, and the porosity is 0.01%-0.5%; the average pore size of the second inner layer is less than 20nm, and the porosity is 0.01%-0.1%; the average pore size of the connecting layer is 80nm-300nm, and the porosity is 1%-15%, preferably 5%-15%; the average pore size of the outer shell is 50nm-1000nm, and the porosity is 5%-15%.
[0010] Preferably, the average particle size D50 of the inner core is 2 μm-5 μm, the thickness of the first inner layer is 500-1300 nm, the thickness of the second inner layer is 550-1900 nm, the thickness of the connecting layer is 100-800 nm, and the thickness of the outer shell is 3000-5000 nm.
[0011] Preferably, the primary particles of the second inner layer have a width of 36nm-50nm, a length of 440nm-700nm, and an aspect ratio of 12-18; the primary particles of the connecting layer have a width of 50-80nm, a length of 500nm-2000nm, and an aspect ratio of 10-20; the primary particles of the outer shell have a width of 150nm-180nm, a length of 500nm-1000nm, and an aspect ratio of 3-7.
[0012] Preferably, the cathode material precursor satisfies one or more of the following conditions:
[0013] a. Particle size: 8.0μm≤D50≤14.0μm;
[0014] b. Particle size distribution: 1.0≤span≤1.5;
[0015] c. Chemical formula is Ni x Co y M z (OH)2, wherein x+y+z=1, 0.7≤x<1, 0≤y≤0.3, 0≤z≤0.3, wherein M is at least one of Mn, Al, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb and Sr.
[0016] The present application also provides a method for preparing the positive electrode material precursor as described above, comprising:
[0017] Under the protection of inert gas, raw materials including a metal salt solution, a complexing agent, and a precipitant are used to react to obtain the inner core, the connecting layer, and the outer shell;
[0018] The reaction for obtaining the inner core is the first reaction, and the pH of the first reaction system is 11-12; the reaction for obtaining the connecting layer and the outer shell is the second reaction, and the pH of the second reaction system is 10-11.
[0019] Preferably, the method for preparing the positive electrode material precursor satisfies one or more of the following conditions:
[0020] A. The concentration of the metal salt solution is 1.0 mol / L-2.0 mol / L;
[0021] B. the complexing agent comprises an aqueous ammonia solution having a concentration of 1 mol / L to 10 mol / L;
[0022] C. the precipitant comprises an aqueous sodium hydroxide solution having a concentration of 5 mol / L-12 mol / L;
[0023] D. In the first reaction, the materials including pure water, precipitant and complexing agent are used as the first base liquid, the pH of the first base liquid is 11-12, and the metal salt solution, the complexing agent and the precipitant are continuously added to the first base liquid to maintain the ammonia concentration of the system at 2g / L-4g / L for reaction;
[0024] E. In the second reaction, the materials including the kernel, pure water, precipitant and complexing agent are used as the second bottom liquid, the pH of the second bottom liquid is 10-11, and the kernel, metal salt solution, complexing agent and precipitant are continuously added to the second bottom liquid to maintain the ammonia concentration of the system at 2g / L-6g / L;
[0025] F. During the first reaction and the second reaction, the flow rate of the metal salt solution is 4.0% / h-7.5% / h of the total capacity of the reaction container;
[0026] G. During the first reaction and the second reaction, the reaction temperature is 50°C-65°C, and the stirring speed is 300r / min-400r / min;
[0027] H. The metal salt solution includes one or more of soluble nitrates, chlorides and sulfates.
[0028] The present application also provides a lithium-ion battery positive electrode material, the raw materials of which include the positive electrode material precursor.
[0029] The present application also provides a lithium-ion battery, the raw material of which is the lithium-ion battery positive electrode material.
[0030] The cathode material precursor provided in this application has the following advantages:
[0031] 1. The first inner layer of the core is loose, and the precursor will shrink internally after high-temperature sintering, forming a central hole inside. The existence of the central hole can slow down the cracking of the particles; the second inner layer is dense, and the primary particles are fine needle-shaped. The dense fine needle shape is conducive to the use of capacity. The outer shell is dense, and the primary particles are spindle-shaped, ensuring the stability of the precursor structure; the loose structure of the connecting layer can effectively buffer the cracking caused by the difference in volume changes between the core and the outer shell of the precursor particles during the charge and discharge process, and improve the material cycle performance.
[0032] 2. At the same time, when the outer shell is dense, the connecting layer makes it easy for the electrolyte to be enriched in the connecting layer, shortening the diffusion path between the core and lithium ions, thereby achieving the purpose of reducing the direct current internal resistance (DCR); it also reduces the side reaction of the electrolyte in the outer shell, thereby inhibiting gas production and improving safety.
[0033] The method for preparing a positive electrode material precursor provided in the present application prepares the positive electrode material precursor with the above-mentioned special structure, which has higher specific capacity, cycle performance and structural stability, lower initial internal resistance, and high capacity and retention rate even under larger currents, reduces the side reaction of the electrolyte in the outer shell, thereby inhibiting gas production and improving battery safety performance, can achieve rapid charging and discharging under large current conditions, and has good application prospects.
[0034] The lithium-ion battery positive electrode material and lithium-ion battery provided in the present application have high capacity, good rate performance and cycle performance, and excellent electrical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0036] Figure 1 This is a SEM image of the cathode material precursor obtained in Example 1;
[0037] Figure 2 CP diagram of the cathode material precursor obtained in Example 1;
[0038] Figure 3 This is a SEM image of the cathode material precursor obtained in Example 2;
[0039] Figure 4 CP diagram of the cathode material precursor obtained in Example 2;
[0040] Figure 5 This is a SEM image of the cathode material precursor obtained in Example 3;
[0041] Figure 6 CP diagram of the cathode material precursor obtained in Example 3;
[0042] Figure 7 This is a SEM image of the positive electrode material precursor obtained in Comparative Example 1;
[0043] Figure 8 This is the CP diagram of the positive electrode material precursor obtained in Comparative Example 1. DETAILED DESCRIPTION
[0044] As used herein:
[0045] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0046] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0047] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0048] In these examples, parts and percentages are by mass unless otherwise indicated.
[0049] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0050] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0051] A positive electrode material precursor comprises a core, a connecting layer and a shell arranged in sequence from the inside to the outside;
[0052] The inner core includes a first inner layer and a second inner layer, the first inner layer is loose, and the primary particles are needle-shaped; the second inner layer is dense, and the primary particles are needle-shaped; the connecting layer is loose, and the primary particles are spindle-shaped or strip-shaped; the outer shell is dense, and the primary particles are spindle-shaped.
[0053] The first inner layer of the core is loose, and the precursor will shrink internally after high-temperature sintering, forming a central hole inside. The existence of the central hole can slow down the cracking of the particles; the second inner layer is dense, and the primary particles are fine needle-shaped. The dense fine needle shape is conducive to the battery capacity prepared by the precursor. The outer shell is dense, and the primary particles are spindle-shaped, ensuring the stability of the precursor structure; the loose structure of the connecting layer can effectively buffer the cracking caused by the difference in volume changes between the core and the outer shell of the precursor particles during the charge and discharge process, and improve the material cycle performance.
[0054] In an optional embodiment, the primary particles of the inner core and the connecting layer are arranged in a disordered manner, and the primary particles of the outer shell are arranged in a radially divergent manner.
[0055] The disordered arrangement of the primary particles in the inner core and the connecting layer is beneficial to the battery capacity prepared by the precursor; the primary particles in the outer shell are arranged radially divergently, which shortens the internal movement path of lithium ions while ensuring the cycle performance.
[0056] In an optional embodiment, the average pore size of the first inner layer is 20nm-200nm, and the porosity is 0.01%-0.5%; the average pore size of the second inner layer is less than 20nm, and the porosity is 0.01%-0.1%; the average pore size of the connecting layer is 80nm-300nm, and the porosity is 1%-15%, preferably 5%-15%; the average pore size of the outer shell is 50nm-1000nm, and the porosity is 5%-15%.
[0057] The porosity of the connecting layer is relatively high, the contact area between the positive electrode material and the electrolyte is larger, and the lithium ion transmission channels are increased, which is conducive to the infiltration of the electrolyte; the loose connecting layer connects the dense outer shell and the dense second inner layer, and the electrolyte is easily enriched in the connecting layer, shortening the diffusion path between the core and lithium ions, thereby achieving the effect of reducing the internal resistance of the battery, improving the battery capacity, and enhancing the rate performance. In addition, it also reduces the side reactions of the electrolyte in the outer shell, thereby inhibiting gas production and improving battery safety.
[0058] Optionally, the average pore size of the first inner layer can be 20nm, 50nm, 100nm, 150nm, 200nm or any value between 20nm-200nm, and the porosity can be 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5% or any value between 0.01%-0.5%; the average pore size of the second inner layer can be 5nm, 10nm, 15nm or any value less than 20nm, and the porosity can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1% or any value between 0.01%-0.1%; the average pore size of the connecting layer can be 80nm, 100nm, 150nm or any value less than 20nm, and the porosity can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1% or any value between 0.01%-0.1%. The average pore size of the shell may be 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm or any value between 50nm-1000nm, and the porosity may be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or any value between 5%-15%.
[0059] In an optional embodiment, the average particle size D50 of the inner core is 2 μm-5 μm, the thickness of the first inner layer is 500-1300 nm, the thickness of the second inner layer is 550-1900 nm, the thickness of the connecting layer is 100-800 nm, and the thickness of the outer shell is 3000-5000 nm.
[0060] In an optional embodiment, the primary particles of the second inner layer have a width of 36nm-50nm, a length of 440nm-700nm, and an aspect ratio of 12-18; the primary particles of the connecting layer have a width of 50-80nm, a length of 500nm-2000nm, and an aspect ratio of 10-20; the primary particles of the outer shell have a width of 150nm-180nm, a length of 500nm-1000nm, and an aspect ratio of 3-7.
[0061] If the aspect ratio of the primary particles is too high, the secondary particles will have low strength; if the aspect ratio is too low, the packing density in the final electrode will be affected. The aspect ratio of each layer of the primary particles in the present application is within an appropriate range, which can shorten the lithium ion migration path inside and outside the primary particles.
[0062] The specific range of porosity and thickness of each layer, the morphology and arrangement of primary particles, the aspect ratio, etc. can not only maintain the structural strength of the material, avoid cracks or even ruptures that lead to reduced cycle performance, but also increase the filling density while taking into account the capacity when preparing the positive electrode.
[0063] The first inner layer is arranged in a disordered and loose state, and the primary particles of the second inner layer are arranged in a disordered and dense state. The thickness of the primary particles is 36-50nm, and the dense fine needle shape is conducive to the utilization of capacity.
[0064] The thickness of the primary particles in the second inner layer determines the porosity range of the connecting layer, and the porosity of the connecting layer is preferably 5%-15%.
[0065] The primary particles of the outer shell are arranged divergently in the radial direction, and the thickness of the primary particles is 150-180nm. The primary particles at this thickness have good circulation performance and stable structure.
[0066] Optionally, the average particle size D50 of the core may be 2 μm, 3 μm, 4 μm, 5 μm or any value between 2 μm and 5 μm, the thickness of the first inner layer may be 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1100 nm, 1200 nm, 1300 nm or any value between 500 and 1300 nm, and the thickness of the second inner layer may be 550 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1100 nm, 1200 nm, 1300 nm or any value between 500 and 1300 nm. The thickness of the connecting layer may be 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm or any value between 100-800nm, and the thickness of the shell may be 3000nm, 3500nm, 4000nm, 4500nm, 5000nm or any value between 3000-5000nm.
[0067] The width of the primary particles of the second inner layer may be 36nm, 40nm, 45nm, 50nm or any value between 36nm-50nm, the length may be 440nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm or any value between 440nm-700nm, and the aspect ratio may be 12, 13, 14, 15, 16, 17, 18 or any value between 12-18; the width of the primary particles of the connecting layer may be 50nm, 60nm, 70nm, 80nm or any value between 50-80nm, the length may be 500nm, 1000nm, 1500nm, 1600nm, 1700nm or any value between 12-18. 00nm, 2000nm or any value between 500nm-2000nm, and the aspect ratio can be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or any value between 10-20; the width of the primary particle of the shell can be 150nm, 160nm, 170nm, 180nm or any value between 150nm-180nm, the length can be 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm or any value between 500nm-1000nm, and the aspect ratio can be 3, 4, 5, 6, 7 or any value between 3-7.
[0068] In an optional embodiment, the cathode material precursor satisfies one or more of the following conditions:
[0069] a. Particle size: 8.0μm≤D50≤14.0μm;
[0070] b. Particle size distribution: 1.0≤span≤1.5;
[0071] c. Chemical formula is Ni x Co y M z (OH)2, wherein x+y+z=1, 0.7≤x<1, 0≤y≤0.3, 0≤z≤0.3, wherein M is at least one of Mn, Al, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb and Sr.
[0072] Optionally, the particle size of the positive electrode material precursor may be 8.0 μm, 8.5 μm, 9 μm, 10 μm, 11 μm, 11.5 μm, 12.0 μm or any value between 8.0 μm ≤ D50 ≤ 12.0 μm; the particle size distribution may be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5 or any value between 1.0 ≤ span ≤ 1.5. In the general chemical formula, x may be 0.7, 0.8, 0.9 or any value greater than or equal to 0.7 and less than 1, y may be 0, 0.1, 0.2, 0.3 or any value greater than or equal to 0 and less than or equal to 0.3, and z may be 0, 0.1, 0.2, 0.3 or any value greater than or equal to 0 and less than or equal to 0.3.
[0073] The present application also provides a method for preparing the positive electrode material precursor, comprising:
[0074] Under the protection of inert gas, raw materials including a metal salt solution, a complexing agent, and a precipitant are used to react to obtain the inner core, the connecting layer, and the outer shell;
[0075] The reaction for obtaining the inner core is the first reaction, and the pH of the first reaction system is 11-12; the reaction for obtaining the connecting layer and the outer shell is the second reaction, and the pH of the second reaction system is 10-11.
[0076] The method adopts a continuous method to form seed crystals, and adjusts the thickness of the second inner layer primary particles by adjusting the ammonia concentration under the conditions specified in the present application, thereby adjusting the porosity of the connection layer by adjusting the thickness of the second inner layer primary particles.
[0077] Optionally, the pH of the first reaction system can be 11.0, 11.1, 11.2, 11.3, 11.4, 11.5, 11.6, 11.7, 11.8, 11.9, 12 or any value between 11-12; the pH of the second reaction system can independently be 10, 10.1, 10.2, 10.3, 10.4, 10.5, 10.6, 10.7, 10.8, 10.9, 11 or any value between 10-11.
[0078] In an optional embodiment, the method for preparing the positive electrode material precursor satisfies one or more of the following conditions:
[0079] A. The concentration of the metal salt solution is 1.0 mol / L-2.0 mol / L;
[0080] B. the complexing agent comprises an aqueous ammonia solution having a concentration of 1 mol / L to 10 mol / L;
[0081] C. the precipitant comprises an aqueous sodium hydroxide solution having a concentration of 5 mol / L-12 mol / L;
[0082] D. In the first reaction, the materials including pure water, precipitant and complexing agent are used as the first base liquid, the pH of the first base liquid is 11-12, and the metal salt solution, the complexing agent and the precipitant are continuously added to the first base liquid to maintain the ammonia concentration of the system at 2g / L-4g / L for reaction;
[0083] E. In the second reaction, the materials including the kernel, pure water, precipitant and complexing agent are used as the second bottom liquid, the pH of the second bottom liquid is 10-11, and the kernel, metal salt solution, complexing agent and precipitant are continuously added to the second bottom liquid to maintain the ammonia concentration of the system at 2g / L-6g / L;
[0084] F. During the first reaction and the second reaction, the flow rate of the metal salt solution is 4.0% / h-7.5% / h of the total capacity of the reaction container;
[0085] G. During the first reaction and the second reaction, the reaction temperature is 50°C-65°C, and the stirring speed is 300r / min-400r / min;
[0086] H. The metal salt solution includes one or more of soluble nitrates, chlorides and sulfates.
[0087] It should be noted that: when the first reaction begins, affected by the concentration of each substance in the system and the reaction process, a loose first inner layer is first formed; as the reaction proceeds, a second inner layer with finer primary particles and denser arrangement is formed around the loose first inner layer, and finally the inner core is obtained; when the inner core is put into the reactor for the second reaction, the primary particles first become coarser and then finer, and a loose connection layer is formed between the inner core and the outer shell, and then an outer shell with different porosity and pore size is gradually formed around the connection layer. It can be understood that the number of connection layers formed by the method provided in this application can be multiple layers, and is not limited to the structure provided in the specification.
[0088] Optionally, the concentration of the metal salt solution may be 1.0 mol / L, 1.5 mol / L, 2.0 mol / L or any value between 1.0 mol / L and 2.0 mol / L; the concentration of the complexing agent may be 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L or any value between 1 mol / L and 10 mol / L; the concentration of the precipitant may be 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L, 12 mol / L or any value between 5 mol / L and 12 mol / L;
[0089] In the first reaction, the ammonia concentration of the system is maintained at 2g / L, 3g / L, 4g / L or 2g / L-4g / L for reaction; the pH of the first base solution can be 11.0, 11.1, 11.2, 11.3, 11.4, 11.5, 11.6, 11.7, 11.8, 11.9, 12 or any value between 11-12; the pH of the second base solution can be 10.0, 10.1, 10.2, 10.3, 10.4, 10.5, 10.6, 10.7, 10.8, 10.9, 11.0 or 10-11, and the ammonia concentration of the system is maintained at 2g / L, 3g / L, 4g / L, 5g / L, 6g / L or 2g / L-6g / L; the flow rate of the metal salt solution can be 4.0% / h, 4.5% / h, 5.0% / h, 5.5% / h, 6.0% / h, 6.5% / h, 7.0% / h, 7.5% / h or 4.0% / h-7.5% / h of the total capacity of the reaction container; during the reaction process, the reaction temperature can be 50°C, 55°C, 60°C, 65°C or 50°C-65°C, and the stirring speed can be 300r / min, 350r / min, 400r / min or 300r / min-400r / min.
[0090] The present application also provides a lithium-ion battery positive electrode material, the raw materials of which include the positive electrode material precursor.
[0091] The present application also provides a lithium-ion battery, the raw material of which is the lithium-ion battery positive electrode material.
[0092] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0093] Example 1
[0094] This embodiment provides a positive electrode material precursor, which includes a core, a connecting layer and a shell arranged in sequence from the inside to the outside, and the core includes a first inner layer and a second inner layer. The SEM image and CP image thereof are respectively as shown in FIG. Figure 1 and Figure 2 The preparation method is as follows:
[0095] Step 1: Preparation of solution: Use soluble salts of nickel, cobalt and manganese as raw materials, prepare a 2.0 mol / L nickel-cobalt-manganese mixed solution according to the molar ratio of Ni:Co:Mn=82:12:6, prepare a 5.5 mol / L sodium hydroxide aqueous solution, and prepare a 5 mol / L ammonia aqueous solution as a complexing agent.
[0096] Step 2: First reaction: Add a certain amount of pure water, NaOH solution (concentration 32wt%), and ammonia water (concentration 21wt%) into a reactor, stir evenly under constant temperature conditions to obtain a first bottom liquid with a pH of 11-12, and the stirring speed is 360r / min; pass an inert gas to protect the first bottom liquid, and use a circulating magnetic pump to uniformly add the nickel-cobalt-manganese mixed solution, ammonia water, and NaOH solution into the first bottom liquid reactor, and continuously feed and discharge. During the reaction, the pH is controlled to be within the range of 11.50-11.80 and the ammonia concentration is fluctuated within the range of 3-4g / L by fine-tuning the flow rate of ammonia water and NaOH solution to maintain particle size stability. After the reaction is stable, prepare to receive the material to obtain a kernel with an average particle size D50 of 3.0μm.
[0097] Step 3: Second reaction: The kernel of step 2 is put into a reactor, and a certain amount of pure water, NaOH solution (concentration 32wt%), and ammonia water (concentration 21wt%) are added into the reactor, and stirred evenly under constant temperature conditions to obtain a second bottom liquid with a pH of 10.4-11, and the stirring speed is 360r / min; inert gas protection is passed through the second bottom liquid, and a nickel-cobalt-manganese mixed solution, a complexing agent, and a precipitant are uniformly added into the second bottom liquid reactor by a circulating magnetic pump. During the reaction, the pH is controlled to fluctuate within the range of 10.4-10.9 and the ammonia concentration is controlled to fluctuate within the range of 3.5-4.5g / L by fine-tuning the flow rate of the precipitant and the complexing agent, and the kernel of step 2 is continuously added to maintain the particle size stability. After the reaction is stable, the material is prepared to obtain a nickel-cobalt-manganese hydroxide with an average particle size D50 of 10.5μm and a particle size distribution span of 1.29.
[0098] Step 4: Post-treatment: The reaction product of step 3 is centrifuged and washed, and then dried and sieved to obtain a product with the chemical formula Ni 0.82 Co 0.12 Mn 0.06 (OH)2 positive electrode material precursor powder sample 1.
[0099] Example 2
[0100] This embodiment provides a positive electrode material precursor, which includes a core, a connecting layer and a shell arranged in sequence from the inside to the outside, and the core includes a first inner layer and a second inner layer. The SEM image and CP image thereof are respectively as shown in FIG. Figure 3 and Figure 4 shown.
[0101] Step 1: Preparation of solution: Use soluble salts of nickel, cobalt and manganese as raw materials, prepare a 2.0 mol / L nickel-cobalt-manganese mixed solution according to the molar ratio of Ni:Co:Mn=85:12:3, prepare a 6 mol / L sodium hydroxide aqueous solution, and prepare a 6.5 mol / L ammonia aqueous solution as a complexing agent.
[0102] Step 2: First reaction: a certain amount of pure water, NaOH solution (concentration 32wt%), and ammonia water (concentration 21wt%) are added to a reactor, and stirred evenly under constant temperature conditions to obtain a first bottom liquid with a pH of 11-12, and the stirring speed is 360r / min; an inert gas is passed through the first bottom liquid for protection, and a nickel-cobalt-manganese mixed solution, a complexing agent, and a precipitant are uniformly added to the first bottom liquid reactor using a circulating magnetic pump, and the materials are continuously fed and discharged. During the reaction, the pH is controlled to fluctuate within the range of 11.8-12 and the ammonia concentration is controlled to fluctuate within the range of 3.5-4.5g / L by fine-tuning the flow rates of the precipitating agent and the complexing agent, so as to maintain the particle size stability. After the reaction is stable, the material is prepared to obtain a core with an average particle size D50 of 3.0μm.
[0103] Step 3: Second reaction: The kernel of step 2 is put into a reactor, and a certain amount of pure water, NaOH solution (concentration 32wt%), and ammonia water (concentration 21wt%) are added into the reactor, and stirred evenly under constant temperature conditions to obtain a second bottom liquid with a pH of 10.2-11, and the stirring speed is 360r / min; inert gas protection is passed through the second bottom liquid, and a nickel-cobalt-manganese mixed solution, a complexing agent, and a precipitant are uniformly added into the second bottom liquid reactor by a circulating magnetic pump. During the reaction, the pH is controlled to be within the range of 10.2-10.5 and the ammonia concentration is fluctuated within the range of 4.5-5.5g / L by fine-tuning the flow rate of the precipitant and the complexing agent, and the kernel of step 2 is continuously added to maintain the particle size stability. After the reaction is stable, the material is prepared to obtain a nickel-cobalt-manganese hydroxide with an average particle size D50 of 10.17μm and a particle size distribution span of 1.35.
[0104] Step 4: Post-treatment: The reaction product of step 3 is centrifuged and washed, and then dried and sieved to obtain a product with the chemical formula Ni 0.85 Co 0.12 Mn 0.03(OH)2 positive electrode material precursor powder sample 2.
[0105] Example 3
[0106] This embodiment provides a positive electrode material precursor, which includes a core, a connecting layer and a shell arranged in sequence from the inside to the outside, and the core includes a first inner layer and a second inner layer. The SEM image and CP image thereof are respectively as shown in FIG. Figure 5 and Figure 6 The preparation steps are as follows:
[0107] Step 1: Preparation of solution: Use soluble salts of nickel, cobalt and manganese as raw materials, prepare a 2.0 mol / L nickel-cobalt-manganese mixed solution according to the molar ratio of Ni:Co:Mn=85:12:3, prepare a 5 mol / L sodium hydroxide aqueous solution, and prepare a 5.5 mol / L ammonia aqueous solution as a complexing agent.
[0108] Step 2: First reaction: Add a certain amount of pure water, NaOH solution (concentration 32wt%), and ammonia water (concentration 21wt%) into a reactor, stir evenly under constant temperature conditions to obtain a first bottom liquid with a pH of 11-12, and the stirring speed is 360r / min; pass an inert gas to protect the first bottom liquid, and use a circulating magnetic pump to uniformly add the nickel-cobalt-manganese mixed solution, ammonia water, and NaOH solution into the first bottom liquid reactor, and continuously feed and discharge. During the reaction, the flow rate of ammonia water and NaOH solution is fine-tuned to control the pH to fluctuate within the range of 11.7-10.8 and the ammonia concentration to fluctuate within the range of 3-4g / L. The reaction is continued until the average particle size D50 reaches 3.0μm, and a core with an average particle size D50 of 3.0μm is obtained.
[0109] Step 3: Second reaction: The kernel of step 2 is put into a reactor, and a certain amount of pure water, NaOH solution (concentration 32wt%), and ammonia water (concentration 21wt%) are added to the reactor, and stirred evenly under constant temperature conditions to obtain a second bottom liquid with a pH of 10.50-10.80, and the stirring speed is 360r / min; inert gas protection is passed to the second bottom liquid, and a nickel-cobalt-manganese mixed solution, a complexing agent, and a precipitant are uniformly added to the second bottom liquid reactor by a circulating magnetic pump. During the reaction, the pH is controlled to fluctuate within the range of 10.50-10.70 and the ammonia concentration is controlled to fluctuate within the range of 2.5-3.5g / L by fine-tuning the flow rate of the precipitant and the complexing agent, and the kernel of step 2 is continuously added to maintain the particle size stability. After the reaction is stable, the material is prepared to obtain a nickel-cobalt-manganese hydroxide with an average particle size D50 of 10.36μm and a particle size distribution span of 1.37.
[0110] Step 4: Post-treatment: The reaction product of step 3 is centrifuged and washed, and then dried and sieved to obtain a product with the chemical formula Ni 0.85 Co0.12 Mn 0.03 (OH)2 positive electrode material precursor powder sample 3.
[0111] Comparative Example 1
[0112] The SEM images and CP images of the positive electrode material precursor provided in this comparative example are as follows: Figure 7 and Figure 8 The preparation steps are as follows:
[0113] Step 1: Preparation of solution: Use soluble salts of nickel, cobalt and manganese as raw materials, prepare a 2.0 mol / L nickel-cobalt-manganese mixed solution according to the molar ratio of Ni:Co:Mn=83:12:5, prepare a 5.5 mol / L sodium hydroxide aqueous solution, and prepare a 5 mol / L ammonia aqueous solution as a complexing agent.
[0114] Step 2: First reaction: a certain amount of pure water, NaOH solution (concentration 32wt%), and ammonia water (concentration 21wt%) are added to a reactor, and stirred evenly under constant temperature conditions to obtain a first bottom liquid with a pH of 11.60-11.70, and the stirring speed is 360r / min; an inert gas is passed through the first bottom liquid for protection, and a nickel-cobalt-manganese mixed solution, ammonia water, and NaOH solution are uniformly added to the first bottom liquid reactor by a circulating magnetic pump. During the reaction, the pH is controlled to be within the range of 11.70-10.80 and the ammonia concentration is fluctuated within the range of 3-4g / L by fine-tuning the flow rates of ammonia water and NaOH solution. During the reaction, the mother liquor is discharged through a concentration device, and the discharge rate is consistent with the total feed amount. The reaction is continued until the average particle size D50 reaches 3.0μm, and then the material is discharged to obtain a kernel with an average particle size D50 of 3.0μm.
[0115] Step 3: Second reaction: The kernel of step 2 is put into a reactor, and a certain amount of pure water, NaOH solution (concentration 32wt%), and ammonia water (concentration 21wt%) are added to the reactor, and stirred evenly under constant temperature conditions to obtain a second bottom liquid with a pH of 10.50-10.80, and the stirring speed is 360r / min; inert gas protection is passed to the second bottom liquid, and a circulating magnetic pump is used to uniformly add the nickel-cobalt-manganese mixed solution, the complexing agent, and the precipitant into the second bottom liquid reactor. During the reaction, the pH is controlled to fluctuate within the range of 10.50-10.70 and the ammonia concentration is controlled to fluctuate within the range of 4-5.5g / L by fine-tuning the flow rate of the precipitant and the complexing agent, and the kernel of step 2 is continuously added to maintain the particle size stability. After the reaction is stable, the material is prepared to obtain a nickel-cobalt-manganese hydroxide with an average particle size D50 of 11.5μm and a particle size distribution span of 1.4.
[0116] Step 4: Post-treatment: The reaction product of step 3 is centrifuged and washed, and then dried and sieved to obtain a product with the chemical formula Ni 0.83Co 0.12 Mn 0.05 (OH)2 positive electrode material precursor powder sample 4.
[0117] Table 1 Parameters of each layer of Examples 1-3 and Comparative Example 1
[0118]
[0119] The relevant parameters of the ternary precursors obtained in Examples 1-3 and Comparative Example 1 are shown in Table 2 below:
[0120] Table 2 Ternary precursor related parameters
[0121]
[0122] The positive electrode material precursors obtained in Examples 1 to 3 and Comparative Example 1 were uniformly mixed with lithium hydroxide in a molar ratio of 1.05:1, sintered in a box furnace under air atmosphere at a sintering temperature of 730° C. for 10 h, and then cooled to room temperature and crushed and sieved to obtain a positive electrode material.
[0123] The electrochemical performance test was conducted using a button-type semi-battery: the above-mentioned positive electrode material, conductive carbon black, and binder PVDF (polyvinylidene fluoride) were mixed into a slurry at a ratio of 8:1:1, and coated on aluminum foil to make a positive electrode sheet. The negative electrode sheet used a metal lithium sheet, and the electrolyte used 1 mol / L LiPF6 / EC:DMC (volume ratio 1:1). The battery shell, positive and negative electrode sheets, diaphragms, springs, and gaskets were assembled into a button-type battery in a vacuum glove box. The electrochemical performance test was conducted using a blue electric test system.
[0124] At room temperature, a 1C cycle test was carried out for 50 weeks under 3.0-4.3V conditions, where the particle strength was evaluated by the volume change rate (the sample was compacted with the same pressure, and the particle size before and after compression was measured by a compaction density meter. The maximum volume share was obtained based on the particle size data. A small maximum volume change indicates good particle strength).
[0125] The performance data of the positive electrode material prepared from the precursor obtained by testing are shown in Table 3 below:
[0126] Table 3 Test data
[0127]
[0128] As can be seen from Table 1, the positive electrode material precursors of Examples 1-3 include a core, a connection layer and a shell from the inside to the outside, wherein the core includes a first inner layer and a second inner layer. The positive electrode material precursor of Comparative Example 1 includes only a shell and a core, because the core of Comparative Example 1 is synthesized by an intermittent method, and the primary particles of the second inner layer formed by it are thick strips and arranged in disorder. When the core is put into the reactor for the second reaction, the primary particles gradually become finer, and there is no obvious connection layer between the core and the shell when the shell is generated; while the cores of Examples 1-3 of the present application are formed by a continuous method, and the primary particles of the second inner layer formed by it are fine needles and densely arranged. When the core is put into the reactor for the second reaction, the primary particles first become thicker and then become thinner, and a loose connection layer will be formed between the core and the shell. It can be seen from Table 2 and Table 3 that the specific surface area of Examples 1-3 is greater than that of Comparative Example 1, the electrical performance capacity is more than 208 mAh / g, the initial DCR is less than that of Comparative Example 1, and the cycle performance, rate performance and strength are also greater than that of Comparative Example 1. It can be seen that the connection layer with an appropriate porosity and layer thickness range under the precursor structure of the present application is beneficial to the performance of the positive electrode material prepared by the precursor in the battery. In addition, the battery of Comparative Example 1 produces serious gas during the test, which greatly affects the safety performance of the battery.
[0129] In Examples 1-3, the thickness of the primary particles is: Example 3 < Example 1 < Example 2; the order of the porosity of the connecting layer and the layer thickness is: Example 3 < Example 1 < Example 2; it can be seen that the porosity of the connecting layer can be adjusted by adjusting the thickness of the second inner layer primary particles. The thicker the primary particles, the greater the porosity of the connecting layer. Among them, the porosity of the connecting layer under the precursor structure of Example 1 is in an appropriate range, its initial DCR is the lowest, the cycle performance reaches 98.36%, and the rate performance and structural strength are also optimal.
[0130] The positive electrode material precursor provided by the present application has a loose first inner layer in the core. After high-temperature sintering, the precursor will shrink internally and form a central hole inside. The presence of the central hole can slow down the cracking of the particles; the second inner layer is dense, and the primary particles are in the shape of fine needles. The dense fine needles are conducive to the use of capacity. The shell is dense, and the primary particles are spindle-shaped, ensuring the stability of the precursor structure; the loose structure of the connecting layer can effectively buffer the cracking caused by the difference in volume changes between the core and the shell of the precursor particles during the charging and discharging process, and improve the material cycle performance. The primary particles of the core and the connecting layer are arranged in a disordered manner, which is conducive to the use of the battery capacity prepared by the precursor; the primary particles of the shell are arranged radially divergently, which shortens the internal movement path of lithium ions while ensuring the cycle performance.
[0131] At the same time, when the outer shell is dense, the connecting layer makes it easy for the electrolyte to be enriched in the connecting layer, shortening the diffusion path between the core and lithium ions, thereby achieving the purpose of reducing the direct current internal resistance (DCR); it also reduces the side reactions of the electrolyte in the outer shell, thereby inhibiting gas production and improving safety.
[0132] The method for preparing a positive electrode material precursor provided in the present application controls the thickness of the primary particles by controlling the concentration of each substance in the system, and then adjusts the porosity range of the connecting layer to prepare the positive electrode material precursor with the above-mentioned special structure, which has higher specific capacity, cycle performance and structural stability, lower initial internal resistance, and high capacity and retention rate even under higher currents, reduces the side reactions of the electrolyte in the outer shell, thereby inhibiting gas production and improving battery safety performance, and can achieve rapid charging and discharging under high current conditions, and has good application prospects.
[0133] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0134] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A cathode material precursor, characterized in that: It includes a core, a connection layer and a shell which are arranged in sequence from the inside to the outside; The inner core comprises a first inner layer and a second inner layer, the first inner layer is loose, and the primary particles are needle-shaped; the second inner layer is dense, and the primary particles are needle-shaped; the connecting layer is loose, and the primary particles are spindle-shaped or thin strips; the outer shell is dense, and the primary particles are spindle-shaped; The porosity of the first inner layer is 0.12%-0.5%, the porosity of the second inner layer is 0.05%-0.1%, the porosity of the connecting layer is 5.5%-15%, and the porosity of the outer shell is 5%-8.2%; The average particle size D50 of the inner core is 2 μm-5 μm, the thickness of the first inner layer is 500-1300 nm, the thickness of the second inner layer is 550-1900 nm, the thickness of the connecting layer is 100-800 nm, and the thickness of the outer shell is 3000-5000 nm; The primary particles of the second inner layer have a width of 36nm-50nm, a length of 440nm-700nm, and an aspect ratio of 12-18; the primary particles of the connecting layer have a width of 50-80nm, a length of 500nm-2000nm, and an aspect ratio of 10-20; the primary particles of the outer shell have a width of 150nm-180nm, a length of 500nm-1000nm, and an aspect ratio of 3-7; The primary particles of the inner core and the connecting layer are arranged in a disordered manner, and the primary particles of the outer shell are arranged in a radially divergent manner.
2. The cathode material precursor according to claim 1, characterized in that: The average pore size of the first inner layer is 20nm-200nm; the average pore size of the second inner layer is less than 20nm; the average pore size of the connecting layer is 80nm-300nm; and the average pore size of the outer shell is 50nm-1000nm.
3. The cathode material precursor according to claim 1 or 2, characterized in that: The positive electrode material precursor meets one or more of the following conditions: a. Particle size: 8.0μm≤D50≤14.0μm; b. Particle size distribution: 1.0≤span≤1.5; c. Chemical formula is Ni x Co y M z (OH)2, wherein x+y+z=1, 0.7≤x<1, 0≤y≤0.3, 0≤z≤0.3, wherein M is at least one of Mn, Al, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb and Sr.
4. A method for preparing a positive electrode material precursor according to any one of claims 1 to 3, characterized in that: include: Solution preparation: prepare a metal salt solution with a concentration of 1.0mol / L-2.0mol / L, prepare a sodium hydroxide aqueous solution with a concentration of 5mol / L-12mol / L as a precipitant, and prepare an ammonia aqueous solution with a concentration of 1mol / L-10mol / L as a complexing agent; First reaction: mixing and stirring materials including pure water, a precipitant, and a complexing agent to obtain a first base liquid with a pH value of 11-12, with a stirring speed of 300r / min-400r / min; passing an inert gas to protect the first base liquid, and continuously adding the metal salt solution, the complexing agent, and the precipitant to the first base liquid, and adjusting the flow rates of the precipitant and the complexing agent to control the pH of the system to be within the range of 11.50-12 and the ammonia concentration to fluctuate within the range of 2-4g / L, the flow rate of the metal salt solution being 4.0% / h-7.5% / h of the total capacity of the reaction container, and reacting to obtain the inner core; The second reaction: the inner core, pure water, precipitant and complexing agent are mixed and stirred to obtain a second base liquid with a pH of 10-11, and the stirring speed is 300r / min-400r / min; an inert gas is passed through the second base liquid for protection, and a metal salt solution, a complexing agent and a precipitant are continuously added to the second base liquid, and the pH of the system is controlled to be within the range of 10.2-10.9 and the ammonia concentration is fluctuated within the range of 2-6g / L by adjusting the flow rate of the precipitant and the complexing agent. The flow rate of the metal salt solution is 4.0% / h-7.5% / h of the total capacity of the reaction container, and a reaction is carried out to obtain a reaction product.
5. The method for preparing a cathode material precursor according to claim 4, characterized in that: The metal salt solution includes one or more of soluble nitrates, chlorides and sulfates.
6. A positive electrode material for a lithium ion battery, characterized in that: The raw material comprises the positive electrode material precursor as described in any one of claims 1 to 3.
7. A lithium ion battery, characterized in that: The raw materials include the lithium ion battery positive electrode material as claimed in claim 6.
Citation Information
Patent Citations
Positive electrode active material precursor, preparation method thereof, and positive electrode active material
CN111653756A